A Look Back: Preschool perspectives in Kappan. (October 2021) - Preston, Teresa
In this monthly column, Kappan managing editor Teresa Preston looks back at how the magazine has covered early childhood education. Since the 1960s, authors have largely agreed about the benefits of high-quality early childhood education, and there has been general consensus about what such a program should look like. However, expanding access to such programs has remained a challenge .